High level of serum Cripto-1 in hepatocellular carcinoma, especially with hepatitis B virus infection. Issue 35 (August 2018) - Zhang, Yingyu; Xu, Hongqin; Chi, Xiumei; Fan, Yuxiang; Shi, Ying; Niu, Junqi
Abstract: Background: Human Cripto-1 (CR-1), a member of the epidermal growth factor-Cripto-1/FRL-1/Cryptic protein family (EGF-CFC), is highly expressed in a variety of human cancers. We aimed to detect serum CR-1 level in liver diseases especially in hepatocellular carcinoma (HCC) patients. Methods: Serum CR-1 level was Sandwich-type enzyme-linked immuno sorbent assay (ELISA) detected in 330 patients with liver diseases including HCC, cirrhosis, and chronic hepatitis and 50 volunteers without hepatitis B virus (HBV) or hepatitis C virus (HCV) infection as control. Results: The serum CR-1 level was significantly higher in HCC patients than volunteer controls and it was also significantly higher in HBV-related HCC than HCV-related HCC. In addition, serum CR-1 level was correlated with serum alpha-feto-protein (AFP) in HBV-related HCC patients. The serum CR-1 was also higher in cirrhosis and chronic hepatitis than volunteer controls. The serum CR-1 in HBV-related cirrhosis was higher than chronic hepatitis B, but there was no significant difference between HCV-related cirrhosis and chronic hepatitis C. Conclusions: Serum CR-1 was higher in HCC patients and might serve as a complementary biomarker to clinical diagnosis of HBV-related HCC. The high level of serum CR-1 in HBV-related liver disease might be partly attributed to HBV infection.